1997
DOI: 10.1002/(sici)1097-4555(199712)28:12<953::aid-jrs190>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Structure and vibrational properties of tetragonal scheelite NaBi(MoO4)2

Abstract: The structure of the tetragonal crystal was determined. The space group is with cell NaBi(MoO 4 ) 2 I4 6 = S 4 2 dimensions a = 5.267, c = 11.565 and Z = 2. The molybdenum atoms occupy two di †erent sites of symmetry.A 4 6 The Na' and Bi3' cations are situated on two positions with di †erent occupancy factors and are short-range ordered. The IR and Raman polarized spectra are discussed on the basis of the factor group analysis and phonon calculations. The modiÐed Urey-Bradley force Ðeld and potential energy di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 4 publications
4
18
0
Order By: Relevance
“…1 The bands at 193 and 208 cm 1 can be assigned to translational modes (Ca-O) and the 193 cm 1 band possibly also as a translational mode of the WO 4 group. 1,6 The band at 927 cm 1 can be interpreted as the symmetric (WO 4 ) similar to the bands observed at 931 cm 1 observed by Daturi et al 1 and 928 cm 1 by Hanuza et al 6 However, Hanuza et al reported a different assignment and interpreted this band as a combination band without further explanation. 6 Wulfenite has a structure comparable to that of scheelite with the W being replaced by the slightly smaller Mo and the Ca being replaced by Pb.…”
Section: The Mineral Chillagitesupporting
confidence: 75%
“…1 The bands at 193 and 208 cm 1 can be assigned to translational modes (Ca-O) and the 193 cm 1 band possibly also as a translational mode of the WO 4 group. 1,6 The band at 927 cm 1 can be interpreted as the symmetric (WO 4 ) similar to the bands observed at 931 cm 1 observed by Daturi et al 1 and 928 cm 1 by Hanuza et al 6 However, Hanuza et al reported a different assignment and interpreted this band as a combination band without further explanation. 6 Wulfenite has a structure comparable to that of scheelite with the W being replaced by the slightly smaller Mo and the Ca being replaced by Pb.…”
Section: The Mineral Chillagitesupporting
confidence: 75%
“…12 The structure is ideally suited for the formation of solid solutions, as it exhibits significant compositional flexibility. 3 When trivalent ions are substituted for the divalent Ca 2+ ion charge compensation has been found to proceed via coupled substitution with monovalent cations, 10,13,14 e.g. alkali metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on the basis of powder neutron and Xray diffraction data for NaBi(MoO 4 ) 2 [10] and NaBi (WO4) 2 [10,11] reported either Scheelite-like structure with space group I4 1 =a or slightly distorted Scheelite structure with space group I4 [12,13]. From our most recent examination of NaBi(WO 4 ) 2 , however, it is clear that the exact crystal symmetry is I4 1 =a [14] and the previously observed symmetry lowering possibly is due to non-stoichiometry.…”
Section: Introductionmentioning
confidence: 99%